Spectral diagnostics of an optical discharge propagating along a hollow-core optical fibre. (March 2021) - Bufetov, I.A.; Kolyadin, A.N.; Yatsenko, Yu.P.; Kosolapov, A.F.
Abstract: The results of spectral diagnostics of an optical discharge (OD) plasma propagating through a hollow-core revolver fibre under the action of repetitively pulsed laser radiation are presented. The revolver fibre is made of silica glass, with a diameter of the hollow core being 20 μm. The peak values of the laser radiation intensity reach 10 12 W cm −2 at an average Nd : YAG laser power of about 2 W. The time-averaged spectrum of the OD plasma in the visible range has the form of a continuum and is close to the blackbody spectrum with a temperature of 13.3 – 17 kK. The form of the spectrum does not depend on the gas filling of the fibre core (air or argon). In the UV part of the spectrum, lines of neutral silicon are observed, which are indicative of the partial evaporation of the reflecting cladding of the fibre.